Voix de femmes songhay-zarma du Niger - Sandra Bornand (Cahiers Mondes Anciens, 2012)
There is, when a man remarries among the Songhay-Zarma of Niger, a specific ritual for polygamous marriages, called the marcanda, in which women, divided into « big » and « little » wives, engage in a verbal joust and then sing together. During this ritual, singers of captive descent sometimes perform saucy songs. They evoke what is never spoken about in everyday life: sexuality. In this paper I will analyze, from an enunciative and pragmatic perspective, the last song from a performance of thirty-two. This song is interesting for it leads to a quarrel that shows how norms are followed in these captive songs, even though they are transgressive, and how this transgressive space, while bound, is constantly renegociated.